1998
DOI: 10.1162/003465398557663
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental q, Cash Flow, and Investment: Evidence from Farm Panel Data

Abstract: This study used a 1976-1992 panel data set to test whether farm machinery investors face finance constraints. Tests were based on fundamental q investment equations in which cash flow was added as an additional explanatory variable. Results indicated that (1) credit constraints were generally not a problem during the 1970s boom, (2) credit constraints became a problem during the 1980s and early 1990s because of tighter credit and/or more conservative financial managerial styles, (3) the investment-cash flow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 15 publications
(13 reference statements)
7
72
2
1
Order By: Relevance
“…An important consideration in using this model is the selection of the appropriate variables for this vector. In line with other studies such as Benjamin and Phimister (2002) and Bierlen and Featherstone (1998) we include the marginal value product of capital (mvpk) and the sales to capital ratio. The mvpk is defined as in Gilchrist and Himmelberg (1995) as the profit to capital ratio and captures the increments to profitability of an additional unit of capital.…”
Section: Q Model Of Investmentmentioning
confidence: 99%
“…An important consideration in using this model is the selection of the appropriate variables for this vector. In line with other studies such as Benjamin and Phimister (2002) and Bierlen and Featherstone (1998) we include the marginal value product of capital (mvpk) and the sales to capital ratio. The mvpk is defined as in Gilchrist and Himmelberg (1995) as the profit to capital ratio and captures the increments to profitability of an additional unit of capital.…”
Section: Q Model Of Investmentmentioning
confidence: 99%
“…There is a wealth of research on farm investment (e.g., Bierlen & Featherstone, 1998;Benjamin & Phimister, 2002;Petrick, 2004a,b;Latruffe, 2005;Bakucs et al, 2009;Bokusheva et al, 2009;Zynch & Odening, 2009;Latruffe et al, 2010;Hüttel et al, 2010;Bojnec & Latruffe, 2011;Kallas et al, 2012). However, studies dealing with agriculture are generally limited to one country and exclude cross-country comparisons, except for Benjamin & Phimister (2002), who compared France and the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found evidence of farm credit constraints, though the evidence is more suggestive because of unobservability and endogeneity complications (Lambert and Bayda 2005). 4 Evidence shows that new farmers, even when operating relatively efficiently, are more likely to face credit constraints, though there is mixed evidence about whether these constraints rise during economic downturns (Bierlen and Featherstone 1998;Hartarska and Nadolnyak 2012). Among many impacts, credit constraints limit technology adoption and productivity (Briggeman, Towe, and Morehart 2009).…”
Section: Theoretical Motivationmentioning
confidence: 99%